The effects of tolterodine on anterior segment and choroidal thickness in patients with overactive bladder syndrome - Hande Hüsniye Telek; Omer Gokhan Doluoglu; Ayse Burcu; Gulizar Demirok; Firdevs Ornek; Ali Ayyildiz (Therapeutic Advances in Urology, 2017)
Background: To evaluate the effects of tolterodine on anterior segment and choroidal thickness by using the Pentacam system and optical coherence tomography (OCT) (Pentacam). Methods: A total of 122 eyes of 61 patients (34 female; 27 male) were included in the study. All patients underwent a regular ocular examination and intraocular pressure measurements before and after 3 months of antimuscarinic drug tolterodine treatment, in addition, pupil diameter, anterior chamber depth, anterior chamber volume, anterior chamber angle, and lens thickness were measured through Pentacam (Oculus Inc., Wetzlar, Germany) system. Measurements of choroidal thickness were performed by OCT (Spectralis ® , Heidelberg Engineering, Heidelberg, Germany). Results: The mean age was 58.4 ± 7.3 years and 56.5 ± 11.1 years for female and male patients. The mean intraocular pressure was 15.10 ± 2.75 mmHg before treatment and 15.18 ± 2.65 mmHg after treatment. Pupil diameters were 3.09 ± 0.48 mm before treatment and 3.12 ± 0.43 mm after treatment. Anterior chamber depth, before and after treatment were 2.68 ± 0.65 mm and 2.70 ± 0.61 mm. The mean value for subfoveal choroidal thickness was 267.92 ± 81.35 μm before the administration of tolterodine, whereas the mean choroidal thickness was 271.83 ± 75.42 μm after the administration of tolterodine. The alterations in the subfoveal choroidal thickness were not statistically significant ( p = 0.862). Conclusions: After 3 months of therapy with tolterodine, there were no significant changes in anterior segment parameters and choroidal thickness.